Desain Tambang Kuari Batugamping Berongga Di Blok Sawir Tuban Jawa Timur - R. Andy Erwin Wijaya; Dwikorita Karnawati; Srijono Srijono; Wahyu Wilopo (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2015)
The research area is a cavity limestone quarry region, located in Sawir Block, Tuban Regency, EastJava Province. Design of the bench in cavity limestone quarry is extremely determined by rock massquality and slope stability analysis. The aim of this research is designing of the bench of cavitylimestone in the quarry based on equibrilium limit and using slide software added. The research usedquantitative method. To obtain slope stability analysis of limestone needs some parameters. The mainparameters are uniaxial compressive strength of intact rock, GSI, lithology, disturbance factor, unitweight and application for slope (height). To solve this analysis is assisted by Roclab software. TheRoclab is a software for determining rock mass strength based on the generalized Hoek-Brown failurecriterion. Final result of the research will be used for safely mine design of the limestone quarry.